Praktik Nikah Siri dalam Perspektif Sadd Al-Dzari'ah (Studi Kasus di Desa Mandirejo Kecamatan Merakurak Kabupaten Tuban) - Firmansyah, Ade; Faozan, Ahmad (Jurusan Hukum Acara Peradilan dan Kekeluargaan, 2026)
Unregistered marriage (nikah siri) remains a prevalent phenomenon in various regions of Indonesia. Although it is considered religiously valid under classical Islamic jurisprudence because it fulfills the essential pillars and legal requirements of marriage, the absence of official registration creates significant legal issues, particularly concerning the protection of women's and children's rights and the legal certainty of family status. This study aims to examine the practice of nikah siri, identify the factors underlying its occurrence, and analyze it through the analytical framework of Sadd al-Dharā'iʿ (blocking the means to harm). This research employed a qualitative method with an empirical juridical approach. Data were collected through in-depth interviews with three couples involved in unregistered marriages, the Head of the Office of Religious Affairs (KUA), the village head, and a local religious leader in Mandirejo Village, Merakurak District, Tuban Regency. The data were analyzed using Miles and Huberman's interactive analysis model. The findings reveal five major factors contributing to the practice of nikah siri: economic considerations, the prevention of adultery, pending divorce proceedings before the Religious Court, the influence of religious leaders, and unauthorized polygamy. Based on the Sadd al-Dharā'iʿ analysis, marriages motivated by economic reasons with the intention of subsequent legal registration are classified as mafsadah nādir (minor potential harm); those influenced by religious leaders or delayed due to ongoing divorce proceedings are categorized as mafsadah ghālib (predominant potential harm); while unauthorized polygamous marriages constitute mafsadah qaṭ'ī (certain harm) because they substantially undermine legal protection for wives and children. This study demonstrates that marriage registration is an essential legal instrument consistent with the objectives of Maqāṣid al-Sharī'ah. The novelty of this study lies in developing a tiered classification of mafsadah (nādir, ghālib, and qaṭ'ī) as an operational framework of Sadd al-Dharā'iʿ for analyzing various motives underlying nikah siri in the field of Islamic family law.